2014
DOI: 10.1057/dddmp.2014.36
|View full text |Cite
|
Sign up to set email alerts
|

The value of Twitter for sports fans

Abstract: Twitter has become a favourite social media vehicle for sports organizations looking to connect with fans. Less is known, however, about the value of tweets for the fans themselves. This research is a preliminary investigation into assessing this value by attempting to classify sports tweets from the fan perspective, and determining whether there is a relationship between value and team identification (TI). Results revealed that TI significantly influences how much people value specific categories of sports tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 28 publications
0
15
0
1
Order By: Relevance
“…Athletes have been encouraged to adopt a more active approach in their public presentation via social media (e.g., Lebel & Danylchuk, 2012;Smith & Sanderson, 2015) and to focus their "away from the game" presentation on authenticity (Smith & Sanderson, 2015, p. 355). Sport marketing literature has also revealed that social media is aiding organizations and athletes in increasing fan identification (e.g., Meng, Stavros, & Westberg, 2015;Williams, Chinn, & Suleiman, 2014) and brand awareness (e.g., Na, Kunkel, & Doyle, 2020;Pegoraro, Scott, & Burch, 2017). Social media can create unique and powerful opportunities for high-profile athletes to capitalize on through increased athlete-fan interaction (Pegoraro, 2010) in a cost-effective manner (Filo et al, 2015).…”
Section: Social Media and Sportmentioning
confidence: 99%
“…Athletes have been encouraged to adopt a more active approach in their public presentation via social media (e.g., Lebel & Danylchuk, 2012;Smith & Sanderson, 2015) and to focus their "away from the game" presentation on authenticity (Smith & Sanderson, 2015, p. 355). Sport marketing literature has also revealed that social media is aiding organizations and athletes in increasing fan identification (e.g., Meng, Stavros, & Westberg, 2015;Williams, Chinn, & Suleiman, 2014) and brand awareness (e.g., Na, Kunkel, & Doyle, 2020;Pegoraro, Scott, & Burch, 2017). Social media can create unique and powerful opportunities for high-profile athletes to capitalize on through increased athlete-fan interaction (Pegoraro, 2010) in a cost-effective manner (Filo et al, 2015).…”
Section: Social Media and Sportmentioning
confidence: 99%
“…These studies demonstrated how SM can aid RM efforts by creating an environment of two-way ongoing interaction between organizations and consumers. Particularly, as Dixon, Martinez, and Martin (2015) and Williams, Chinn, and Suleiman (2014) stated, the features of SM make it a valuable platform in realizing RM goals that have been long dominated by off-line activities. These features include instantaneity, ubiquity, time unrestrained access (Williams & Chinn, 2010), and simplicity and ease of access, networking, participation, and collaboration (Ngai et al, 2015).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In other words, content analysis is used in evaluating, interpreting and coding textual material into valid data. Content analysis was used in several studies that examined Twitter content to measure athlete-fan interaction (Kassing & Sanderson, 2010), the value of Twitter for sports fans (Williams et al, 2014), athlete endorsements and branding (Carlson & Donovan, 2008;Smith & Sanderson, 2015), uses and gratifications (Clavio, 2008), and athlete communication (Hambrick et al, 2010;Pegoraro, 2010;Seo & Green, 2008). The abundance of studies in this area and the use of the content analysis technique for research in sports show the effective use of this technique to develop beneficial contributions.…”
Section: Content Analysismentioning
confidence: 99%
“…Twitter is the platform that is perhaps most capable of delivering the content regarding the personal and social lives of professional athletes to fans (Hambrick et al, 2010), allowing sport organizations to promote their teams and increase fan engagement (Williams, Chinn, & Suleiman, 2014) and engaging athletes in direct conversations about their lives (Pegoraro, 2010). A variety of studies have concentrated on investigating athlete communication patterns on Twitter.…”
Section: Introductionmentioning
confidence: 99%